Genetic and Epigenetic Regulation of Brain Organoids - Wang, You-Wei; Hu, Nan; Li, Xiao-Hong (Frontiers in Cell and Developmental Biology, 2022)
Reading the mind is one of the most challenging missions in life science. Thanks to stem cell biotechnology, scientists can mimic the development, maturation, signal generation, and function of human brains, with pluripotent stem cells derived from brain organoids. Single-cell RNA sequencing (scRNA-Seq) and multielectrode array (MEA) independently revealed the similarity between brain organoids and immature human brain at early developmental stages, in the context of gene transcription and dynamic network of neuronal signals. Brain organoids provided the unique opportunity to investigate the underlying mechanism of neural differentiation, senescence, and pathogenesis. In this review, we summarized the latest knowledge and technology in the brain organoid field, the current and potential applications in disease models and pre-clinic studies, with emphasizing the importance of transcriptional and epigenetic analysis.